PENGARUH PRICE TO BOOK VALUE, RETURN ON ASSET, EARNING PER SHARE, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PT UNILEVER INDONESIA TBK - Fayzhall, Miyv; Yulia, Yayah; Lestari, Sri; Yanto, Adi (Jurnal Bisnis Manajemen dan Akuntansi, 2025)
This study aims to obtain empirical evidence regarding factors related to stock prices at PT Unilever Indonesia Tbk for the period 2014 - 2024. These factors include price to book value, return on assets, earnings per share and Debt to Equity Ratio which affect stock prices. The research method used in this study is multiple regression. The results of the study indicate that, partially (1) price to book value has a positive and significant effect on stock prices (2) return on assets has a positive and significant effect on stock prices, (3) earnings per share has a positive and significant effect on stock prices, and (3) debt to equity ratio has a negative and significant effect on stock prices at PT Unilever Indonesia Tbk. Simultaneously, price to book value, return on assets, earnings per share, and debt to equity ratio have a significant effect on stock prices at PT Unilever Indonesia Tbk by 92.0%